2012
DOI: 10.1186/1471-230x-12-16
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of a periodontal pathogen, Porphyromonas gingivalis on the pathogenesis of non-alcoholic fatty liver disease

Abstract: BackgroundNon-alcoholic fatty liver disease (NAFLD) is a hepatic manifestation of metabolic syndrome that is closely associated with multiple factors such as obesity, hyperlipidemia and type 2 diabetes mellitus. However, other risk factors for the development of NAFLD are unclear. With the association between periodontal disease and the development of systemic diseases receiving increasing attention recently, we conducted this study to investigate the relationship between NAFLD and infection with Porphyromonas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
310
2
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 239 publications
(328 citation statements)
references
References 32 publications
8
310
2
8
Order By: Relevance
“…Yoneda et al . reported that the detection frequency of P. gingivalis in saliva from NASH patients was significantly higher than that in healthy subjects and that infection by P. gingivalis may be an additional risk factor for NASH (Yoneda et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yoneda et al . reported that the detection frequency of P. gingivalis in saliva from NASH patients was significantly higher than that in healthy subjects and that infection by P. gingivalis may be an additional risk factor for NASH (Yoneda et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…A recent epidemiological study showing that P. gingivalis at high frequency was present in NAFLD/NASH patients suggested a close relationship between periodontitis and NASH (Yoneda et al, 2012). Furusho et al reported acceleration of hepatic inflammation and fibrosis as a result of P. gingivalis infection in the dental pulp of a maxillary molar in mice with fatty liver fed with high‐fat diet (HFD; Furusho et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The normal gut microbiota carries out specific functions in host nutrient metabolism, xenobiotic and drug metabolism, structural integrity maintenance of the gut mucosal barrier, immunomodulation, and protection against pathogens 11, 12, 13, 14, 15. Recently, the gut microbiome has been shown to play a crucial role in health, as well as in diseases such as obesity,16 inflammatory bowel disease,17, 18 diabetes,19, 20 non‐alcoholic fatty liver disease,21, 22, 23 and several types of cancers 24, 25. Experimental evidence indicates that the human intestinal microbiome can influence tumor development and progression in the gastrointestinal tract by damaging DNA, activating oncogenic signaling pathways, producing tumor‐promoting metabolites, and suppressing the antitumor immune response 7, 25, 26, 27, 28, 29.…”
Section: Introductionmentioning
confidence: 99%
“…We emphasize that not only a specific strain of S. mutans but also other species could possibly induce aggravation of NASH. In fact, a specific strain of Porphyromonas gingivalis , one of the major periodontitis-related species, also aggravates NASH conditions in the same mouse model [19]. We will investigate the effects of other bacterial species to the development of NASH conditions in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…All procedures used in the present study were approved by the Animal Care and Use Committee of the Osaka University Graduate School of Dentistry. The effects of intravenous administrations of S. mutans strains on the development of NASH were analysed using a NASH mouse model as previously described [15,19] with some modifications [17]. Briefly, 6-week-old C57BL/6J male mice ( n  = 94; Charles River Japan, Tokyo, Japan) were randomly divided into either the HFD plus phosphate-buffered saline (PBS) administration group ( n  = 42) or HFD plus TW871-treated group ( n  = 52).…”
Section: Methodsmentioning
confidence: 99%